PENGARUH PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI, ASIMETRI INFORMASI DAN MORALITAS INDIVIDU TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI : STUDI EMPIRIS PADA ORGANISASI PERANGKAT DAERAH (OPD) KABUPATEN KAMPAR - Uci Lestari; Novita Indrawati; Al Azhar A (Jurnal Ekonomi, 2018)
This study aims to examine the effect of internal control, compensation suitability, information asymmetry and individual morality to the tendency of accounting fraud. The population in this study was 28 OPD in Kampar Regency, and the method used in sample selection was sensus sampling. The number of samples in this study was 120 respondents. This study used primary data by dissemination of the questionnaires. Technical analysis for test hypothesis that used in this study was multiple linear regression analysis. The result of this research showed that internal control, compansation suitability and individual morality negative effect on the tendency of accounting fraud, while information asymmetry positive effect on the tendency of accounting fraud.